Analisis Kemampuan Pemecahan Masalah Pada Materi Kekonvergenan Barisan Dan Deret Bilangan Real - khasanah, binti anisaul; amorie, jean; sholikhah, nur (JURNAL e-DuMath, 2019)
The research aimed to describe the problems solving level of students math education study program STKIP Muhammadiyah Pringsewu Lampung in the academic year of 2018-2019 in solving the convergence of sequences and series of real numbers on the advanced calculus subject. Data analysis techniques were used to analyze the results of students' answers in achieving the indicators of problem solving skills. The result obtained the phase of understanding the problems in the amount of 86%, the phase of choosing the right strategy to overcome the problems was 69%, the process of solving the problem correctly and systematically was 45%, the phase of re-examining the precision The results showed that the ability of students to understand the problem was very good, the ability of students to choose the right strategy to solve good problems, the ability of students to solve problems correctly and systematically enough, and the ability of students to re-check the accuracy of the strategy chosen and the truth of problem solving still very less